The case for technology policy: A tentative evaluation - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper is a tentative summary and appraisal of the main theoretical arguments and empirical evidence for/against an industrial policy in support of high-tech industries. The paper reviews arguments based on endogenous growth theory and strategic trade theory and surveys the most relevant pieces of empirical evidence, notably on external learning effects and international rent-shifting. The author concludes that there is no solid empirical basis for sector-specific technology policies, but that one might make a sensible case for non-discriminatory government support to knowledge creation by private firms, e.g., through a generous tax treatment of private spending on research and development.
Keywords: O3; O30; O31; 330; Forschungs- und Technologiepolitik; Industriepolitik; Neue Wachstumstheorie; Strategische Handelspolitik; Halbleiter; Luftfahrtindustrie; Theorie; Welt